THE GROWTH OF RELIGIOUS EDUCATION IN THE BURKHARAN EMIRATE DURING THE RULE OF AMIR SHAKHMURAD AND AMIR HAIDAR (Scientific journal of the Fergana State University, 2025)
The period from the establishment of the Bukhara Emirate, specifically the latter half of the 18th century to the 1920s, focuses on examining the historical significance of religious scholars in the governance, societal dynamics, economy, and culture of the Bukhara Emirate. The historical examination of the scientific literature and articles enables categorization into three distinct periods based on the timing of study, substance, domain, and methodological approach. Contemporary historians, particularly emerging scholars in historiography focused on manuscript sources, while acknowledging the contributions of previous researchers, are tasked with examining the history, socio-political dynamics, and culture of our country's medieval period from a novel perspective. This endeavor emphasizes truthfulness, historicity, and scientific rigor, grounded in the principles of objectivity, and represents a significant challenge for modern historiography.